Mentorship Scheme – a Novel Approach for Plugging the Gap in Differential Attainment for Psychiatry Core Trainees in East Midlands - Samreen Samad; Awhangansi Sewanu; Champion Seun-Fadipe; Nick Long; Ian Yanson (BJPsych Open)
Aims: The MRCPsych results report and GMC annual report on trainee performance highlighted that UK PMQ candidates perform better than OS PMQ candidates and that White candidates perform better compared with candidates with other ethnic backgrounds. A mentoring scheme was designed as a proposed solution to bridge the gap of differential attainment in Core trainees in Psychiatry with a focus on improving ARCP outcome and Exam Pass rate in Psychiatry.